Technology of Personal Education - as a factor of Development - Quvvataliyev Mirzamakhmud Khabibulloyevich (Genius Publishing Group, 2023)
This article presents the scientific theoretical basis of the formation of psychological characteristics of a person. The methods and aspects of forming the essence of personality aspects of girls and boys are highlighted.
Keywords: Person; tradition; customs; feelings